Conceptual interactive learning tools based on computer simulators - Zazula, Damjan (Informatica (Ljubljana), 1999)
An existent computer-based simulator may serve double purpose: simulating the basic phenomenon that was conceptually modelled by the simulator, and offeringits inherent teaching characterisctics at the same time. In this paper we describe shortly the basic concepts of a simulator of electromyographic signals (EMGs) which was, first, written for a single-user environment in C++ and later ported to Java and interactive network environment. At this stage it became natural that the Java application was upgraded by the features of a teaching and learning tool. Such an integration was possible in a client-server approach providing the network users with a compact facility for generating the EMG components and signals, and learning about the electro-physiological phenomena in parallel.
Keywords: modeliranje; simulacije; učenje; learning; Java; elektromiografija